Drugs: A Very Short Introduction - Iversen, Leslie (New York Oxford University Press, 2001)
During the 20th century, the introduction of new medicines for the treatment of infections, heart disease, cancer, and mental illnesses and the oral contraceptive have altered all of our lives. This work gives an account of how drugs work in the body, and reviews both legal (alcohol, nicotine, and caffeine) and illegal recreational drugs.
Includes Index and Illustrations.
Keywords: Drugs -- Popular works